(untitled) (Fiep Bulletin - online, 2013)
Descriptive epidemiological study of type with a qualitative approach that aims to know the profile of users of morbidity seen at the clinic of the Division of Healthcare - DSA, the Department of Assistance to the server’s UFRN, in 2006. The data were obtained through the Doctors Office software, which exists in the DSA, and exported to Microsoft Excel 2003, and analyzed by Epi- Info version 6.0. 4716 years attendance has been made, with a predominance of users servers (49.9%), followed by a dependent (44.7%) and students (5.4%). Most users of the DSA are male, married, with ages between 20 to 59 years old, white, natural capital and present occupation compatible with the average level of schooling. The first five groups of diseases of the ICD-10, evident in the study, for the general population, from were: diseases of the genitourinary system, the apparatus circulatory, infectious and parasitic, endocrine and nutrition, and finally to the musculoskeletal system. In this sense, we consider the existence of two distinct profiles of morbidity, where we have a side of the servers with an average age of 43 to 59 years, with prevalence of female and chronic degenerative diseases. On the other side of the population dependent and students where the average age is below 30 years, presents a higher prevalence of male sex and diseases are prevalent in acute characterization. So know the profile of users of the DAS, highlights the need to intervene politically to change the reality.